1999
DOI: 10.1128/mcb.19.10.6566
|View full text |Cite
|
Sign up to set email alerts
|

Both TEL and AML-1 Contribute Repression Domains to the t(12;21) Fusion Protein

Abstract: t(12;21) is the most frequent translocation found in pediatric B-cell acute lymphoblastic leukemias. This translocation fuses a putative repressor domain from the TEL DNA-binding protein to nearly all of the AML-1B transcription factor. Here, we demonstrate that fusion of the TEL pointed domain to the GAL4 DNA-binding domain resulted in sequence-specific transcriptional repression, indicating that the pointed domain is a portable repression motif. The TEL pointed domain functioned equally well when the GAL4 DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 64 publications
3
180
0
Order By: Relevance
“…Interestingly, the inhibition is similar to that observed when overexpressing AML1. Previous studies have shown that the HLH domain is required for the transcriptional repression of AML1-dependent promoters by TEL-AML1 Fears et al, 1997;Fenrick et al, 1999;Uchida et al, 1999). TEL-AML1 lacking a HLH domain activates AML1-dependent transcription, albeit not as effectively as AML1.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, the inhibition is similar to that observed when overexpressing AML1. Previous studies have shown that the HLH domain is required for the transcriptional repression of AML1-dependent promoters by TEL-AML1 Fears et al, 1997;Fenrick et al, 1999;Uchida et al, 1999). TEL-AML1 lacking a HLH domain activates AML1-dependent transcription, albeit not as effectively as AML1.…”
Section: Discussionmentioning
confidence: 93%
“…To determine which domains are required for TEL-AML1 activity in vitro and in vivo, we generated a number of deletion mutants based on previous studies (Fenrick et al, 1999;Uchida et al, 1999;Guidez et al, 2000) (Figure 1). These studies found that deletion of the runt homology domain (RHD) domain abolished TEL-AML1 binding to AML1 consensus sequences, whereas deletions of the C-terminal transactivation domain of AML1 or the HLH domain of TEL did not affect the ability of TEL-AML1 to bind to DNA (Uchida et al, 1999).…”
Section: Expression Of Domain Deletion Mutants Of Tel-aml1 Using Retrmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that another ets factor, TEL, can act as a transcriptional repressor, in part through interaction with a co-repressor through its pointed domain (Fenrick et al, 1999).…”
Section: An Elf3 Ets Domain Mutant Partially Abrogates Repression Of mentioning
confidence: 99%
“…The other class of TEL's partner genes encodes transcription factors such as RUNX1/AML1, which codes for a DNA binding subunit of the core binding factor (CBF; Speck, 2001). The TEL-AML1 fusion protein oligomerizes and exhibits repressive transcription properties and dominant-negative effect on normal AML1 activity (Hiebert et al, 1996;Fenrick et al, 1999). We recently described a TEL-ARNT fusion protein in a case of human acute myeloblastic leukemia (AML; Salomon-Nguyen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%